Chemical composition of various Ephedra species - Ibragic, Saida (Bosn J Basic Med Sci, 2015)
The medicinal significance of Ephedra is based on the sympathomimetic properties of ephedrine (E) alkaloids. Pharmacological effects depend on the phytocomposition of individual Ephedra species. The aim of this study was to measure the total alkaloids content (TAC), total phenolics content (TPC), and total flavonoids content (TFC) and determine their relationship in dry herb of Ephedra major, Ephedra distachya subsp. helvetica, Ephedra monosperma, Ephedra fragilis, Ephedra foeminea, Ephedra alata, Ephedra altissima and Ephedra foliata. Nowadays, medicinal use of Ephedrae herba is limited, but the abuse of its psychostimulants is rising. In this study, TAC, TPC and TFC were determined using spectrophotometric methods. For the first time, ultra-performance liquid chromatography with ultraviolet detection (UPLC-UV) was used for separation and quantification of E-type alkaloids of various Ephedra species. The highest TPC and TFC were found in E. alata (53.3 ± 0.1 mg Gallic acid equivalents/g dry weight, 2.8 mg quercetin equivalents/g dry weight, respectively). The total content of E and pseudoephedrine determined by UPLC-UV varied between 20.8 mg/g dry weight (E. distachya subsp. helvetica) and 34.7 mg/g dry weight (E. monosperma). The variable content and ratio between secondary metabolites determined in different Ephedra species reflects their metabolic activities. Utilization of UPLC-UV unveiled that this technique is sensitive, selective, and useful for separation and quantification of different alkaloids in complex biological matrixes. The limit of detection was 5 ng. Application of UPLC-UV can be recommended in quick analyses of E-type alkaloids in forensic medicine and quality control of pharmaceutical preparations.